The Cambridge companion to contemporary African American literature - Goyal, Yogita (Cambridge ; New York, NY : Cambridge University Press, 2024)
"African American literary production has changed in astounding ways since the 1970s. This book provides a systematic and vibrant account of the range and achievements of contemporary Black writers. It considers the history, practice, and future directions of the field"--
African American citizenship in the post-civil rights era / Margo Crawford -- The politics of class / Rolland Murray -- Rethinking post-racialism / Aida Levy-Hussen -- Afro-futurism and the speculative turn / Madhu Dubey -- The Black lyric / Anthony Reed -- Neo-slave imaginaries / Christopher Freeburg -- Incarceration and confinement literature / Patrick Elliott Alexander -- Satire, comedy, and critique / Derek Maus -- Popular romance and literary undergrounds / Aneeka Henderson -- Feminist intersections / Sheri Marie Harrison -- Queer bodies in time / GerShun Avilez -- Global and diasporic worldmaking / Nadia Ellis -- African American soundscapes / Shana Redmond -- African American literature and visual culture / Hayley O'Malley -- The affective turn / Lauren Michele Jackson -- Print culture and literary sociology / Kinohi Nishikawa -- Digital and new media cultures of protest / Marisa Parham.
Includes bibliographical references.
Keywords: American literature -- African American authors -- History and criticism